ANALISIS PENGARUH PENANAMAN MODAL DALAM NEGERI (PMDN), PENANAMAN MODAL ASING (PMA), PENGELUARAN PEMERINTAH DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI D.I. YOGYAKARTA (Tahun 1996 – 2012) - Bambang Muqsyithu Wihda; Dwisetia Poerwono (Universitas Diponegoro, 2014)
ABSTRACTThis study aims to determine the effects of domestic investment (DCI ) , foreign direct investment ( FDI ) , government expenditure and manpower on economic growth in Special District of Yogyakarta. This research was conducted within a period of 17 years , starting from 1996 to 2012 .This study uses linear regression analysis by the method of Ordinary Least Square ( OLS ). Partial testing using t-test statistics and simultaneous testing using the F-test statistic. It also performed classical assumption , where all the test using SPSS 17 program tools.The results shows that domestic investment is positive and not significant effect at 0.019724 , foreign direct investment is positive and significant effect at 0.142914 , government expenditure is positive and not significant effect at 0.140872 and manpower is positive and not significant effect at 0.055265 to economic growth in Special District of Yogyakarta. Based on the results of the F test at the 95% confidence level ( α = 5 % ) obtained F value of 19.88998 calculated with a probability value of 0.000 means that the variable domestic investment , foreign investment , government expenditure , and manpower are significant effect to economic growth in D.I. Yogyakarta.